Red Dirt Thinking on Aspiration and Success - Sam Osborne; John Guenther (The Australian Journal of Indigenous Education, 2013)
This article sets the scene for the series of five articles on ‘red dirt thinking’. It first introduces the idea behind red dirt thinking as opposed to ‘blue sky thinking’. Both accept that there are any number of creative and expansive solutions and possibilities to identified challenges — in this case, the challenge of improving education in very remote Aboriginal and Torres Strait Island schools. However, the authors believe that creative thinking needs to be grounded in the reality of the local community context in order to be relevant. This article draws on emerging data from the Remote Education Systems project (a project within the Cooperative Research Centre for Remote Economic Participation — CRC-REP) and highlights further questions and challenges we wish to address across the life of the project. It is part of a collection of papers presented on the theme ‘Red Dirt Thinking’. The red dirt of remote Australia is where thinking for the CRC-REP's Remote Education Systems research project emerged. This article will examine the various public positions that exist in regard to the aspirations of young remote Aboriginal and Torres Strait Islander Australians, and consider the wider views that are held in terms of what constitutes educational ‘success’. We explore the models of thinking and assumptions that underpin this public dialogue and contrast these ideas to the ideas that are being shared by remote Aboriginal educators and local community members through the work of the Remote Education Systems project. We will consider the implications and relevance of the aspiration and success debate for the remote Australian context and propose approaches and key questions for improved practice and innovation in relation to delivering a more ‘successful’ education for remote students. The authors begin by posing the simple question: How would, and can remote educators build aspiration and success? The wisdom of several commentators on remote education in Australia is presented in terms of a set of simple solutions to a straightforward problem. The assumptions behind these simple solutions are often unstated, and part of this article's role is to highlight the assumptions that common arguments for solutions are premised on. Further to the above question, we will also consider the question: In remote communities where Aboriginal and Torres Strait Islander students live and learn, how is success defined? Is there language that corresponds to the western philosophical meanings of success? Having considered some possible alternatives, based on the early findings of the Remote Education Systems project research, the authors then pose the question: How would educators teach for these alternative measures of success? The answers to these questions are still forthcoming. However, as the research process reveals further insights in relation to these questions, it may be possible for all those involved in remote education to approach the ‘problem’ of remote education using a different lens. The lens may be smeared with red dirt, but it will enable people involved in the system to develop creative solutions in a challenging and rich environment.